Uneven Technical Progress and Unemployment - Hans Gersbach; Achim Schniewind (Institute for the Study of Labor (IZA), 2002)
In a two-sector-economy with real wage rigidity, we examine how technical progress in one sector affects aggregate unemployment. We show that aggregate unemployment decreases for uneven technical change in the case of Cobb-Douglas production functions. For every type of technical progress there are also elasticities of substitution in production and utility functions leading to a rise in unemployment. Moreover, we identify polar cases when unemployment strongly decreases.
Keywords: E24; D58; L13; J60; 330; uneven technical progress; elasticities of substitution; unemployment; Theorie der Arbeitslosigkeit; Technischer Fortschritt; Mehr-Sektoren-Modell; Faktorsubstitution; Lohnrigidität; Beschäftigungseffekt; Theorie